Strategies to combat wheat rust in India - Bhardwaj, S C; Prashar, M; Singh, S B; Kumar, Subodh; Sharma, Y P (Indian Farming, 2015)
The strategies of deploying rust resistant varieties based on pathotype distribution have proved successful in managing wheat rusts. However, wheat rusts are international pathogens which do not respect geographical barriers and spread through the continents what to say of countries. Wheat rusts are enemies of mankind. Therefore, there is a need to have more international cooperation for the exchange of information, analysis of pathotype situation, evaluation of germplasm and exchange of germplasm. Rust trap nurseries like SAARC wheat disease trap nursery initiated by India need to be strengthened and to be used effectively for this purpose.